Systematic Literature Review: Teknik Deteksi Serangan Siber Berbasis AI dan Data Mining - Risqa Taufik (PT. Hasba Edukasi Mandiri, 2025)
Cyber attack detection is one of the main challenges in ensuring information security in the digital era. With the increasing complexity and frequency of attacks, techniques based on artificial intelligence (AI) and data mining have become effective solutions for quickly and accurately identifying threats. This paper reviews various cyber attack detection techniques utilizing AI and data mining, including machine learning, neural networks, deep learning, and data mining techniques such as clustering, classification, and anomaly detection. The study also discusses the strengths and weaknesses of each technique, as well as trends and challenges in their real-world implementation. The results of the literature review indicate that the combination of AI and data mining techniques can offer a more effective and adaptive solution to the evolving cyber threats.